2020
DOI: 10.1177/1753193420936591
|View full text |Cite
|
Sign up to set email alerts
|

Surgical fixation of fractures of the distal radius within 2 weeks reduces postoperative finger stiffness

Abstract: Locked anterior plating remains the most common form of surgical fixation for displaced fractures of the distal radius. We hypothesized that delayed surgical fixation later than 2 weeks after injury contributes to poorer patient outcomes for patients with displaced or intra-articular fractures of the distal radius. We conducted a retrospective cohort study of 158 patients who underwent locked anterior plating for an intra-articular or displaced fracture of the distal radius using multiple regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… 29 , 30 Although there is not a specific, proven threshold in the literature for when DRFs need to be operatively fixated, having a modest reduction and attempt to reduce time to surgery to less than 14 days is a reasonable goal, and has been demonstrated to be within a safe window of time for operative fixation. 31 Given that the average time to surgery for the country hospital patients in our study was 16.2 days, we feel that a modest 2-day improvement is certainly possible. Attempts to accomplish this goal could include more frequent attempts to contact patients that initially no-show for appointments and attempts to schedule sooner follow-up for patients after initial date of injury.…”
Section: Discussionmentioning
confidence: 78%
“… 29 , 30 Although there is not a specific, proven threshold in the literature for when DRFs need to be operatively fixated, having a modest reduction and attempt to reduce time to surgery to less than 14 days is a reasonable goal, and has been demonstrated to be within a safe window of time for operative fixation. 31 Given that the average time to surgery for the country hospital patients in our study was 16.2 days, we feel that a modest 2-day improvement is certainly possible. Attempts to accomplish this goal could include more frequent attempts to contact patients that initially no-show for appointments and attempts to schedule sooner follow-up for patients after initial date of injury.…”
Section: Discussionmentioning
confidence: 78%
“…The significant differences in PROMs were found at a surgical delay of seven days or more and two different PROM tools were utilized, DASH 23,28 and The Michigan Hand Outcomes Questionnaire 16 . Clinical outcomes included increased finger and thumb stiffness (>2 wk delay), 20 decreased functional outcomes in flexion and ulnar deviation at a delay of greater than one week, 23 and more than triple the odds of experiencing chronic pain with a one-week delay to surgery 24 . One study found that surgeons reported greater procedural difficulty with a delay greater than one week 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the five trials that found significant differences in time to surgery, four trials found significant differences at a surgical delay of greater than one week, 16,23,24,28 and one trial found significant differences in patients with a surgical delay of greater than two weeks. 20 One study reported radiographic significance, 23 three studies reported significant differences among PROMs, 16,23,28 and all five studies reported differences in clinical outcomes 16,20,23,24,28 (Table 3). The significant differences in PROMs were found at a surgical delay of seven days or more and two different PROM tools were utilized, DASH 23,28 and The Michigan Hand Outcomes Questionnaire.…”
Section: Time To Surgery and Definition Of Delaymentioning
confidence: 99%
“…A study by Ashdown et al. showed that surgical fixation of DRFs within 2 weeks reduces postoperative finger stiffness [ 8 ]. Another study by Sirniö et al.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal timing for internal fixation among patients with DRFs had yet to be determined. Early surgery shows superior outcomes and is recommended in most cases [ 8 , 9 , 10 , 11 ]. However, some studies have shown that delayed fixation affects only short-term outcomes and is indistinguishable in long-term functional results [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%